Pengembangan Media Pembelajaran Ispring Suite 9 pada Mata Pelajaran Pendidikan Agama Islam dalam Peningkatan Hasil Belajar Siswa - Umroh, Hijjatul; Sanjaya, Budi; Ridwan, Ahmad (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2023)
This research is Research and Development (R&D) research with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model developed by Lee & Owens. With data analysis techniques, namely qualitative and quantitative data obtained from product quality assessment questionnaires and hypothesis testing using one-way ANOVA. This research shows the level of suitability of the iSpring Suite 9 learning media in the subject of Islamic Religious Education, the average assessment by material experts is 4.61 indicating the